A high-resolution X-ray microscope system for performance evaluation of scintillator plates. (27th September 2022) - Yamamoto, Seiichi; Yoshino, Masao; Kamada, Kei; Yajima, Ryuga; Yoshikawa, Akira; Sagisaka, Mayu; Kataoka, Jun
Abstract: In the development of new scintillators for X-ray imaging, a high-resolution and highly efficient system is required to evaluate the performance of the scintillator plates. For this purpose, we developed a high-resolution X-ray microscope system. The developed compact X-ray microscope system is based on a magnifying unit and a cooled charge-coupled device (CCD) camera, combined with a small industrial X-ray irradiation system. Using this system, we carried out imaging of three scintillator plates and evaluated their spatial resolution. Each scintillator plates was set in front of the lens of the objective, X-rays were irradiated to the scintillator plates, and transmission images of masks were acquired. The measured spatial resolution of the scintillator plates varied from 16 μm to 30 μm, depending on the type of scintillator plate. The focus size of the X-ray tube had an almost negligible effect on the spatial resolution of the images for the evaluated scintillator plates.